Diagnosis of a community monitoring proposal in La Muerte mountain range (Costa Rica) (Biocenosis, 2023)
Different human activities modify the natural processes of the environment; therefore, it is necessary to record changes, possible causes and design strategies to mitigate their impact. To follow up on the changes, data is continuously recorded through participatory monitoring, which is very effective for the conservation of biological resources, since the community and people involved are the ones who best know their territory and the organisms living there. The main purpose of this study was to carry out the first stage of the design of a participatory monitoring initiative with the communities bordering the “Cerro Vueltas” Biological Reserve, located in “Macizo de la Muerte”, in the provinces of Cartago and San José, in the Talamanca mountain range, Costa Rica. Semi-structured interviews were conducted by means of a survey with 18 questions, 12 of which being semi-open-ended and six closed-ended. The results of the surveys show that tourism in this area is one of the main economic activities for the community. In addition, it is acknowledged that a series of threats related to climate change, land use change and mainly due to the expansion of coffee growing areas and purchase of land by foreigners are impacting their environment and tourism as an economic activity.
Keywords: citizen science; ecosystem benefits; ecotourism; biodiversity; conservation